A Dyadic Investigation of Depressed Affect and Interspousal Behavior in Couples With Chronic Back Pain. Issue 10 (27th November 2021) - Post, Kristina M; Smith, David A; Burns, John W; Porter, Laura S; Keefe, Francis J
Abstract: Background: Depression and marital discord are characteristic not only of individuals with chronic low back pain (ICPs) but also of their spouses. Purpose: We examined actor–partner interdependence models to evaluate associations among depressed affect and criticism and support of partners at the same time point (concurrent effects) and 3 hr later (lagged effects). Fully dyadic models were used to account for both within-person and cross-spouse associations among depressed affect, criticism, and support for ICPs and spouses. We also examined the direction of the relationships (depressed affect predicting behavior and behavior predicting depressed affect) all while controlling for pain intensity, pain behavior, and the prior dependent variable. Methods: ICPs ( n = 105) and their spouses completed electronic diary measures of depressed affect and behavior (criticism and support) five times a day for 2 weeks. Hierarchical linear modeling with person-mean centering was used for data analysis. Results: Within the same 3 hr epoch, more depressed affect was related to higher criticism and generally less support. Lagged analyses suggested bidirectional relationships between spouse's own depressed affect and spouse's own criticism of ICPs. Spouse depressed affect was also associated with decreased support received from ICPs. Pain behavior and pain intensity were also related to depressed affect, criticism, and support especially concurrently. Conclusions: Theories and interventions need to address not only ICP depressed affect but also spouse depressed affect, as spouse depressed affect may be a stress generating precursor to criticism and support. Abstract : Criticism and decreased support were associated with feeling depressed especially for spouses of individuals with pain. Importantly, spouse's criticism predicted spouse depression and vice versa.